2020
DOI: 10.1017/ice.2020.348
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-resistant pathogens associated with urinary tract infections in nursing homes: Summary of data reported to the National Healthcare Safety Network Long-Term Care Facility Component, 2013–2017

Abstract: Objective: Antibiotic resistance (AR) is a growing and highly prevalent problem in nursing homes. We describe selected AR phenotypes from pathogens causing urinary tract infections (UTIs) reported by nursing homes to the National Healthcare Safety Network (NHSN). Design: Pathogens and antibiotic susceptibility testing results for UTI events in nursing homes between January 2013 and December 2017 were analyzed. The pathogen distribution and pooled mean proportion of isolates that tested r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…In our analysis, in both periods, the most common organisms were Escherichia coli (56.6% vs 51.6%), Klebsiella pneumoniae (14.7% vs 16.5%), Enterococcus faecalis (11.6% vs 12%), and Pseudomonas aeruginosa (4.5% vs 5%). This spectrum is similar to the previous studies by Meena et al [ 12 ], and Shah et al [ 6 ] from India; Sorlozano et al [ 13 ] from Spain; Eure et al [ 14 ] and Sharma et al [ 15 ] from Grenada; and Lagunas-Rangel [ 16 ] from Mexico. Most authors have reported Escherichia coli and Klebsiella pneumoniae among the top three causative organisms for UTI (Table 4 ), which is similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…In our analysis, in both periods, the most common organisms were Escherichia coli (56.6% vs 51.6%), Klebsiella pneumoniae (14.7% vs 16.5%), Enterococcus faecalis (11.6% vs 12%), and Pseudomonas aeruginosa (4.5% vs 5%). This spectrum is similar to the previous studies by Meena et al [ 12 ], and Shah et al [ 6 ] from India; Sorlozano et al [ 13 ] from Spain; Eure et al [ 14 ] and Sharma et al [ 15 ] from Grenada; and Lagunas-Rangel [ 16 ] from Mexico. Most authors have reported Escherichia coli and Klebsiella pneumoniae among the top three causative organisms for UTI (Table 4 ), which is similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…CDC's NHSN is the nation's surveillance program for health careeassociated conditions. 17,18 For the purposes of monitoring the pandemic, in collaboration with CMS, NHSN was able to rapidly expand from approximately 3000 nursing homes performing monthly reporting to receiving weekly reporting from the approximately 15,400 CMS-certified nursing homes and more than 1000 additional facilities for assisted living and intermediate care for individuals with intellectual disabilities. 9,19,20 The results of this study and others 7,8,21 demonstrate the importance of NHSN as a national surveillance infrastructure for nursing homes and other health care delivery populations.…”
Section: Discussionmentioning
confidence: 99%
“…S. saprophyticus is a more frequent cause of UTI in otherwise healthy young women ( 7 , 16 ). Antibiotic-resistant isolates, particularly methicillin-resistant S. aureus (MRSA), are widely disseminated and are common causes of community-acquired MRSA infections, including UTI ( 11 , 17 22 ). However, our knowledge on the pathogenesis and host response during UTI caused by staphylococci is limited ( 16 , 23 ).…”
Section: Introductionmentioning
confidence: 99%